Relationships between soil quality indicators, redox properties, and bioactivity of humic substances of soils under integrated farming, livestock, and forestry - Altoé Baldotto, Marihus; Estrela Borges Baldotto, Lílian (Revista Ceres, 2025)
Once it is stabilized in the soil, organic matter minimizes limitations of Brazilian Oxisols, such as low cation exchange capacity, low nutrient availability, toxicity due to high aluminum content, and phosphate adsorption. Moreover, humified organic matter fractions are bioactive. It is, therefore, important to evaluate the biostimulant ability of compounds present in soil carbon stocks to develop sustainable technologies for tropical agriculture based on renewable natural resources. The objective of this research was to correlate some soil quality indicators, redox properties, and bioactivity of humic acids isolated from integrated farming, livestock, and forestry systems aiming to understand the mechanisms involved in plant stimulation by humified organic matter. Carbon stocks and their stability were determined from oxidation by dichromatometry and iodometry, respectively. Bioactivity was assessed using yield data of corn indicator plants. The results indicated that when native-like forests were reintroduced instead of pastureland, soil carbon stocks and their stability increased along with overall improvements in soil fertility, chemical and physical properties, and soil biodiversity. The bioactivity of humic substances isolated from soils used in integrated crop, livestock, and forestry management was higher than that of soils derived from pastures or eucalyptus alone.